USULAN PERANCANGAN TATA LETAK LANTAI PRODUKSI DENGAN METODE SYSTEMATIC LAYOUT PLANNING DAN BLOCPLAN PADA PRODUK CUTTING STEEL PIPE DI CV. ANUGRAH JAYA SEJAHTERA CILEUNGSI: Perancangan Tata Letak Fasilitas - Silmi Saffanah Sadjugo; Rani Aulia Imran; Ayu Anggraeni Sibarani (Universitas Putera Batam, 2023)
Facility layout is a procedure for establishing factory facilities to support the smooth running of a production process. CV. ABC is an automotive manufacturing industry that produces cutting steel pipe products, part of motorcycle spare parts. This study aims to design a new facility layout for the production of cutting steel pipe products to minimize the distance of material movement and the moment of movement, as well as the company's desire to increase production targets by adjusting machine requirements. In designing the layout of this proposed facility using the BLOCPLAN algorithm software. Based on the calculation of machine requirements the measurement process lacks 1 person, the cutting process in the automatic machine section lacks 2 machines, while for the Manual machine section lacks 1 machine. The Manual cutting process, there is a shortage of 1 machine. A quality control and packing on automatic machines require 1 person and 3 people. Meanwhile, packing in the Manual machine section requires as many as 2 people. Material transfer distance between departments is calculated using the rectilinear method. The moment of material movement is calculated by multiplying the displacement distance by the frequency. The total distance of material movement in the existing layout results in 148.2 meters with a displacement moment of 18981.3 meters per month. Meanwhile, the redesign using the BLOCPLAN algorithm software resulted in a total material transfer distance of 110.88 meters with a displacement moment of 15621.21 meters per month.